PENINGKATAN PEMAHAMAN KURIKULUM 2013 BAGI GURU SEKOLAH DASAR - Widodo, Noto; Nugroho, Setiya (BERDIKARI : Jurnal Inovasi dan Penerapan Ipteks, 2019)
This community service activity aims at developing skills for elementary school (SD) teachers of Muhammadiyah Sirojuddin in using information technology media, namely Microsoft Excel to process the data of the assessment result to the report in accordance with curriculum 2013. The method used was through information technology training divided into three stages, namely: (1) description making of each grade on the fields of affective, cognitive, and psychomotor; (2) submitting grade of affective, cognitive, and psychomotor fields; (3) converting grade from number to descriptive form. The community service was carried out in six times of meetings with 17 teachers of SD Muhammadiyah Sirojuddin. The result of the service community are 15 teachers are helped in understanding curriculum 2013 and grade conversion process based on Microsoft Excel program. The result of the descriptive grade is the one that will be benefitted by the teachers as data input in the report in accordance with curriculum 2013.